PENGARUH BRAND IMAGE DAN PRODUCT KNOWLEDGE TERHADAP PURCHASE INTENTION DENGAN GREEN PRICE SEBAGAI MODERATING VARIABEL PADA PRODUK THE BODY SHOP - Dwi Danesty Deccasari; Dian Mawar; Marli Marli (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to study the Effect of Brand Image and Product Knowledge on Purchasing Intention with Green Prices as a moderating variable on The Body Shop products both simultaneously and partially to consumers of The Body Shop in Malang City. The sample used in this study was 103 respondents. The analytical tool used is multiple linear regression analysis and Moderating Regression Analysis (MRA) with Green Price as moderating. The results showed that brand image has a positive effect on purchase intention (H1), product knowledge has a positive effect on purchase intention (H2), green prices have a positive effect on purchase intention (H3), brand image has a positive effect on green prices as a moderating variable (H4), Product Knowledge has a positive effect on green prices as a moderating variable (H5). The results of the interaction testing after using the Moderating Regression Analysis (MRA) indicate that green prices as moderating variables have a significant influence and strengthen the positive influence on the independent variable with the dependent variable. Due to green prices greatly affect the level of consumer purchase intention on products Shop body that is environmentally friendly and can be recycled is also safe for beauty and health that is expected by consumers.